Hocus pocus - Desrosiers, Sylvie, 1954- (Kids Can Press, 2011)
A mischievous little rabbit from a magician's hat sets his eye on a bunch of fresh carrots on the magician's kitchen counter, but before he can enjoy them he must get past a grumpy dog that is intent on keeping the clever little rabbit away.